2023
DOI: 10.1667/rade-22-00183.1
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rg3 Sensitizes Nasopharyngeal Carcinoma Cells to Radiation by Suppressing Epithelial Mesenchymal Transition

Abstract: Radioresistance restrains the therapeutic effect of nasopharyngeal carcinoma (NPC). Ginsenoside Rg3 (Rg3), an active pharmaceutical component extracted from ginseng, shows antitumor effects in various cancers. In this study, we aimed to determine whether Rg3 sensitized NPC cells to radiation and to explore the possible mechanisms. Our results revealed that Rg3 increased radiosensitivity in both HNE1 and CNE2 cell lines. Radiation-induced epithelial mesenchymal transition (EMT) in NPC cells and Rg3 blocked this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…GS-Rg3 can also increase the sensitivity of pancreatic cancer to gemcitabine by decreasing ZFP91-mediated TSPY like 2 instability ( 44 ). Moreover, GS-Rg3 can enhance the radiosensitivity of cancer cells in different tumor types, such as lung, breast and nasopharyngeal cancer ( 45 47 ). Additionally, GS-Rg3 combined with artemisinin can inhibit STAT3 signal transduction in hepatocellular carcinoma cancer cells, synergistically reduce the viability of cells, induce apoptosis and inhibit the growth of mouse hepatocellular carcinoma ( 48 ).…”
Section: Antitumor Effects Of Gs-rg3mentioning
confidence: 99%
“…GS-Rg3 can also increase the sensitivity of pancreatic cancer to gemcitabine by decreasing ZFP91-mediated TSPY like 2 instability ( 44 ). Moreover, GS-Rg3 can enhance the radiosensitivity of cancer cells in different tumor types, such as lung, breast and nasopharyngeal cancer ( 45 47 ). Additionally, GS-Rg3 combined with artemisinin can inhibit STAT3 signal transduction in hepatocellular carcinoma cancer cells, synergistically reduce the viability of cells, induce apoptosis and inhibit the growth of mouse hepatocellular carcinoma ( 48 ).…”
Section: Antitumor Effects Of Gs-rg3mentioning
confidence: 99%
“…explored the sensitizing therapeutic effect of GRg3 combined with radiotherapy. The results showed that GRg3 could block radiotherapy-induced EMT, reduce the nuclear translocation of EGFR and the expression of DNA-dependent protein kinases, significantly promote the apoptosis of HNE1 and CNE2 cells; thus, GRg3 could be further promoted as a potential radiotherapy sensitizer ( 22 ). In lung cancer cells, GRg3 and GRg5 also have radiosensitizing effects.…”
Section: Chinese Herb Monomermentioning
confidence: 99%